Molecular phylogeny of Acer monspessulanum L. subspecies from Iran inferred using the ITS region of nuclear ribosomal DNA - HANIF KHADEMI; IRAJ MEHREGAN; MOSTOFA ASSADI; TAHER NEJADSATARI; SHAHIN ZARRE (Biodiversitas Journal of Biological Diversity, 2016)
Khademi H, Mehregan I, Assadi M, Nejadsatari T, Zarre S. 2015. Molecular phylogeny of Acer monspessulanum L. subspecies from Iran inferred using the ITS region of nuclear ribosomal DNA. Biodiversitas 17: 16-23. This study was carried out on the Acer monspessulanum complex growing wild in Iran. Internal transcribed spacer (ITS) sequences for 75 samples representing five different subspecies of Acer monspessulanum were analyzed. Beside this, 86 previously published ITS sequences from GenBank were used to test the monophyly of the complex worldwide. Phylogenetic analyses were conducted using Bayesian inference and maximum parsimony. The results indicate that most samples of A. monspessulanum species from Iran were part of a monophyletic clade with 8 samples of A. ibericum from Georgia, A. hyrcanum from Iran and one of A. sempervirens from Greece (PP= 1; BS= 79%). Our results indicate that use of morphological characteristics coupled with molecular data will be most effective.